Return to work in multi-ethnic breast cancer survivors - a qualitative inquiry - Tan, Foo Lan; Loh, Siew Yim; Tin, Tin Su; Veloo, V.W.; Ng, Lee Luan (West Asia Organization for Cancer Prevention, 2012)
Introduction: Return-to-work (RTW) can be a problematic occupational issue with detrimental impact on the quality of life of previously-employed breast cancer survivors. This study explored barriers and facilitators encountered during the RTW process in the area of cancer survivorship. Materials and Methods: Six focus groups were conducted using a semi-structured interview guide on 40 informants (employed multiethnic survivors). Survivors were stratified into three groups for successfully RTW, and another three groups of survivors who were unable to return to work. Each of the three groups was ethnically homogeneous. Thematic analysis using a constant comparative approach was aided by in vivo software. Results: Participants shared numerous barriers and facilitators which directly or interactively affect RTW. Key barriers were physical-psychological after-effects of treatment, fear of potential environment hazards, high physical job demand, intrusive negative thoughts and overprotective family. Key facilitators were social support, employer support, and regard for financial independence. Across ethnic groups, the main facilitators were financial-independence (for Chinese), and socialisation opportunity (for Malay). A key barrier was after-effects of treatment, expressed across all ethnic groups. Conclusions: Numerous barriers were identified in the non-RTW survivors. Health professionals and especially occupational therapists should be consulted to assist the increasing survivors by providing occupational rehabilitation to enhance RTW amongst employed survivors. Future research to identify prognostic factors can guide clinical efforts to restore cancer survivors to their desired level/type of occupational functioning for productivity and wellbeing.